Antibiofilm formation activity of purified lectin from wheat seeds (Triticum aestivum) against Candida albicans causing oral candidiasis (Texas Journal of Multidisciplinary Studies, 2022)
Wheat seeds (Triticum aestivum) are among the grains with a high lectin concentration. The sort with the highest lectin content had the lectin removed and purified. It was purified via fractionation with 60% NH3SO4 saturation then loadeded on DEAE-Cellulose column followed by Sepharose-6B size exclusion chromatography, and a yield of 61.5% with specific activity of 853.3 U/mg. Oral candidiasis led to the isolation of seven different Candida albicans isolates, all of which produced variable quantities of biofilm. With percentages of biofilm inhibition ranging from 23 to 44% with 50 µg/ml. The isolated lectin demonstrated antibiofilm efficacy against all Candida albicans isolates. The inhibition grew with increasing doses, reaching 65-88% at 200 µg/ml. such that lectin can be used to treat an oral cavity that is infected with Candida albicans.